2023
DOI: 10.1113/ep090776
|View full text |Cite
|
Sign up to set email alerts
|

The mechanosensitive ion channel ASIC2 mediates both proprioceptive sensing and spinal alignment

Abstract: New Findings What is the central question of this study? Proprioception is initiated by mechanosensitive neurons. However, the identities of the molecular players that mediate proprioceptive sensing are largely unknown. Here, we aimed to identify potential mechanosensitive ion channels that mediate proprioceptive signalling. What is the main finding and its importance? We identify the mechanosensitive ion channel ASIC2 as a key component in proprioceptive sensing and a regulator of spine alignment. AbstractB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…It is noteworthy that ASIC2 ion channels are present on proprioceptive Type Ia afferent terminals [ 48 ]. The ablation of ASIC2 will result in altered-muscle-spindle-derived stretch responses and motor coordination, in addition to impairment to spinal alignment [ 49 ]. This paper proposed that Piezo2 is needed for mechanostransductory signaling on proprioceptive neurons and ASIC2 modulates this signaling [ 49 ].…”
Section: Piezo2 Channelopathy Piezo2–piezo1 Crosstalk and Syndecansmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that ASIC2 ion channels are present on proprioceptive Type Ia afferent terminals [ 48 ]. The ablation of ASIC2 will result in altered-muscle-spindle-derived stretch responses and motor coordination, in addition to impairment to spinal alignment [ 49 ]. This paper proposed that Piezo2 is needed for mechanostransductory signaling on proprioceptive neurons and ASIC2 modulates this signaling [ 49 ].…”
Section: Piezo2 Channelopathy Piezo2–piezo1 Crosstalk and Syndecansmentioning
confidence: 99%
“…The ablation of ASIC2 will result in altered-muscle-spindle-derived stretch responses and motor coordination, in addition to impairment to spinal alignment [ 49 ]. This paper proposed that Piezo2 is needed for mechanostransductory signaling on proprioceptive neurons and ASIC2 modulates this signaling [ 49 ]. In support, a loss of function on Piezo2 also causes impaired proprioception [ 50 ] and scoliosis [ 51 ].…”
Section: Piezo2 Channelopathy Piezo2–piezo1 Crosstalk and Syndecansmentioning
confidence: 99%
“…Another scRNA‐seq study of proprioceptors showed that ASIC1 and ASIC2 were close to the afferent endings of both MS and GTO (Oliver et al., 2021 ). A recent study showed that ASIC2‐knockout mice exhibited skeletal malalignment and impaired proprioceptive performance in beam‐walking tasks and gait coordination, whereas the morphology of MS and GTO, locomotion abilities and treadmill walking distance were similar to that for wild‐type mice (Bornstein et al., 2023 ). However, the role of ASIC1 in proprioception remains to be determined.…”
Section: Updating the Roles Of Asics In Proprioceptionmentioning
confidence: 99%
“…For example, using substrate deformation‐driven neurite stretch and micropipette‐guided ultrasound in knockout mouse models of ASIC subtypes, researchers in Chih‐Cheng Chen's laboratory analysed the roles of ASIC3 and ASIC1a in muscle spindles and other organs relying on mechanotransduction (Lin et al., 2024 ). Using in vivo proprioception‐related behavioural assays and ex vivo electrophysiological analyses of muscle spindles, mice lacking ASIC2 were shown to display impairments in muscle spindle responses to stretch and motor coordination tasks, demonstrating that ASIC2s are required for normal muscle spindle function (Bornstein, Watkins et al., 2024 ). Moreover, these mice also revealed skeletal deficits, including an impaired spinal alignment (Bornstein, Watkins et al., 2024 ), further supporting the important role of proprioception for the development or maintenance of the skeletal system.…”
mentioning
confidence: 99%
“…Using in vivo proprioception‐related behavioural assays and ex vivo electrophysiological analyses of muscle spindles, mice lacking ASIC2 were shown to display impairments in muscle spindle responses to stretch and motor coordination tasks, demonstrating that ASIC2s are required for normal muscle spindle function (Bornstein, Watkins et al., 2024 ). Moreover, these mice also revealed skeletal deficits, including an impaired spinal alignment (Bornstein, Watkins et al., 2024 ), further supporting the important role of proprioception for the development or maintenance of the skeletal system. Collectively, these studies identify ASICs as key components in mechanosensation.…”
mentioning
confidence: 99%